Caracterização das proporções anatômicas e tempo de trânsito gastrointestinal do apaiari e do acarÁ-bandeira - Fabregat, Thiago El Hadi Perez; do Nascimento, Thiago Matias Torres [UNESP]; Pereira, Thiago Scremin [UNESP]; Barbosa, Andressa Steffen (My University, 2015)
This study aimed to characterize the digestive tract anatomic and the gastrointestinal transit time of oscar (Astronotus ocellatus) and angelfish (Pterophyllum scalare), relating the results with the feeding habit. For this purpose two experiments were conducted. First the stomach somatic index and the intestinal coefficient were evaluated for the two species. In the second experiment the gastrointestinal transit time was evaluated. The stomach somatic index averages were higher (P<0.05) for the oscar (0.54 ± 0.14) compared to the angelfish (0.19 ± 0.05). On the other hand the intestinal coefficient was lower (P<0.05) in the oscar (0.46 ± 0.07) than in the angelfish (0.99 ± 0.22). Furthermore, the oscar the gastrointestinal transit time (10 h) was faster (P<0.05) in relation to the angelfish (12 h). From the results is possible to conclude that the oscar digestive tract was more adapted for carnivorous habits, and the angelfish approaches more of a generalist omnivore. Moreover, variations in the size of the digestive system organs could affect the gastrointestinal transit time.
Gastrointestinal tract evaluations for oscar and angelfish: Anatomic proportions and transit time
Keywords: Anatomy; Astronotus ocellatus; Freshwater fish; Nutrition; Ornamental fish; Pterophyllum scalare